MicroRNAs orchestrating host and vector-borne protozoan interactions: bridging immune modulation and cross-species communication - Li, Jianyong; Zhu, Feng; Zhang, Jian (Frontiers in Immunology, 2025)
Vector-borne protozoan diseases, such as malaria, leishmaniasis, and trypanosomiasis, continue to impose a substantial burden on global health. The intricate molecular interplay between hosts and protozoan pathogens critically shapes disease progression and clinical outcomes, yet the regulatory mechanisms governing these interactions remain incompletely elucidated. Emerging evidence highlights microRNAs (miRNAs) as key epigenetic modulators of host-protozoan cross-talk. Infection with protozoans triggers dynamic alterations in host miRNA expression profiles, which subsequently fine-tune innate and adaptive immune responses through regulation of macrophage polarization, neutrophil activity, and T and B cell differentiation. Beyond their immunomodulatory roles, miRNAs can directly target protozoan genes to restrict pathogen replication, while protozoa, in turn, exploit host miRNA networks to evade immune surveillance and facilitate persistent infection. This bidirectional miRNA-mediated dialogue not only deepens our understanding of host-pathogen interactions but also unveils new avenues for clinical innovation. The distinctive expression patterns and functional versatility of miRNAs position them as promising candidates for diagnostic biomarkers, therapeutic targets, and next-generation intervention strategies. In this review, we synthesize the current knowledge on how miRNAs orchestrate the complex interplay between hosts and protozoa, and explore their translational potential in combating these neglected diseases.